Global Strategies for Climate-Neutral Business: Green Public Relations and Digital Solutions - Iryna Maksymova; Tatiana Petrishyna; Alexander Bai (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Aims: The study aims to systematically investigate and substantiate the integration of green PR, digital transformation, and ESG principles into a complex strategy for achieving climate neutrality by global business. It seeks to explore the synergies and potential leverage points among these three domains to outline a holistic approach that corporations can adopt to mitigate their environmental impact in the digital era. Study Design: The research utilizes a qualitative approach, incorporating an extensive review of existing data, case studies, and statistical analysis to explore green strategies, ESG targets and green PR within digital solutions in order to satisfy corporate sustainability and climate neutrality. Methodology: The methodology includes a detailed literature review to gather insights on digital transformation, green PR, and ESG strategies in business; analysis of examples of corporations implementing sustainability strategies; and analysis of open data related to corporate expenditures on green transitions, the effectiveness of digital solutions for sustainability, and surveys of environmental awareness provided by reputable global agencies. Results: The study identifies the main challenges faced by corporations in achieving climate neutrality. It highlights the effectiveness of digital solutions in managing climate sustainability and the critical role of green PR in fostering environmental responsibility and engaging stakeholders. The research also presents data indicating a significant consumer demand for environmentally friendly products and corporate practices. Conclusion: The authors conclude that digital transformation and green PR are complementary strategies that create synergies in the pursuit of sustainable development. They emphasize the importance of integrating these strategies with ESG principles to develop effective corporate sustainability strategies. The study provides recommendations for leveraging digital innovations to enhance ESG initiatives, aiming to achieve climate neutrality.